ANALISIS MINAT BELAJAR MATEMATIKA SISWA SMP KELAS IX PADA MATERI GRAFIK FUNGSI KUADRAT BERBANTUAN SOFTWARE GEOGEBRA - Khodijah, Siti Sarah; Setiawan, Wahyu (Universitas Papua, 2020)
The purpose of this research’s to analyze students interest in mathematical leaning by the matery Grafik Fungsi Kuadrat (Graphs of Quadratic Functions) assisted by GeoGebra sofware. In this research, the researcher used descriptive research method, descriptive research method is the research that generates descriptive data through the percentage of student answers that contain 5 indicators of learning interest scale students by given poll. The population of this research were 28 students of nineth grade of SMP Bingkai Cendikia Cililin. Research data were collected by using the scale of learning interest of students in GeoGebra sofware assisted with mathematics learning that contains 20 questions each 10 positive and negative questions. The result of the data analysis could be concluded that there is a positive impact on students interest in learning mathematics assisted with GeoGebra sofware. The result of the data analysis showed by the average percentage of answers of students who agree of positive statement’s 49%, then the response of agree average of 67%, and then disagree response’s 10,8%, while for strongly disagreeing responses of 6.5%.